Biotin–specific synthetic receptors prepared using molecular imprinti - Piletska, Elena V.; Piletsky, Sergey A.; Karim, K.; Terpetschnig, E.; Turner, Anthony P. F. (Elsevier Science B.V., Amsterdam., 2004)
The composition of new molecularly imprinted polymers (MIPs) specific for biotin was optimised using molecular modelling software. Three functional monomers: methacrylic acid (MAA), 2-(trifluoromethyl)acrylic acid (TFAA) and 2-acrylamido- 2-methyl-propanesulfonic acid (AMPSA), which demonstrated the highest binding scores with biotin, were tested on their ability to generate specific binding sites. The imprinted polymers were photografted to the surface of polystyrene microspheres in water. The affinity of the synthetic "receptor" sites was evaluated in binding experiments using horseradish peroxidase-labelled biotin. A good correlation was found between the modelling results and the performance of the materials in the template rebinding study. The dissociation constants for all MIPs were 1.4-16.8 nM, which is sufficient for most analytical applications where biotin is used as a label.
Keywords: Computational design; Photografting polymerisation